Mathematical model and optimize technique to enhance the performance of football teams - Ahmmed Saadi (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
This paper represents to derive mathematical model depends on the real state to provide one example of world cup football of women 2019. The specified USA football team as a good example, due to it represents the best winner team in this cup. In this work make active interaction between modeling and optimization depend on actual state activities of football team through the cup. Specified six female footballers who represented the USA football team who participated or scored eight goals from the role of sixteen until final role. The outcomes of this study increases the performance of the USA team to 14.2 %, reduce the cost of efforts of duties of high quality players that need to keep their activities for a long time and organize some duties to some supporting players to provide a wide range to score many goals and reduce the pressure against the main players. This study needs from researchers of the sport field and football coaches to read and analysis the outcomes of this study and evaluate it in actual state.